Theology, religion, and Dungeons & Dragons: explorations of the sacred through fantasy worlds - Donahue-Martens, Scott; Simonson, Brandon (Theology, Religion, and Pop Culture, 2025)
"This volume describes Dungeons & Dragons as a generative and creative space by exploring the tabletop role-playing game's intersections with the academic disciplines of Theology and Religious Studies. Readers might not gain advantage on all religion checks, but they will recognize the deeply formative potential of the game"-- Provided by publisher